Colecistectomía Laparoscópica En Paciente Geriátrico. - Salgado Romero, William (2012)
Objective: To determine the morbidity and mortality of the elective patients surgically operated on gallbladder lithiasis for laparoscopic surgery at the Trujitlo Regional Teaching Hospital during 2005-2010. Method: A cross-sectional descriptive study was carried out in patients older than 60 years with a diagnosis of vesicular lithiasis undergoing elective laparoscopic cholecystectomy. Results: A total of 121 cases were studied, of which 56.2% are female patients (n = 68). The most frequent age group is 60-69 years (71.9%). The extreme ages were 60 and 77 years, with a mean age of 67.3 years. The most frequent pathological antecedents were cardiovascular diseases (46.3%); Hypertension (34.7%) and endocrine metabolic diseases such as diabetes mellitus (31.4%), osteoarthrosis played an important role. Many patients coexisted with more than two pathologies. Cardiovascular complications such as tachycardia (37.2%) and hypertension (25.6%) also predominated in the intraoperative period. In the immediate postoperative period, nausea (25.6%) and vomiting (29.8%) predominated. Operative site infection was the most frequent in the late postoperative period. Conclusion: Age was not a surgical limitation. The most frequent complications were cardiovascular complications, but no significant repercussion in patients.